Bioethics for the regulation of assisted reproduction techniques and gestational surrogacy in Mexico - San Vicente Parada, Aida del Carmen (2023)
Reproductive techniques allow people to realise their desire to become parents; however, these techniques are expensive and the biological material of other humans is needed to fulfil this desire. This generates several situations: biocapitalism, the mercantilisation and instrumentalisation of the body and socio-economic gaps; it also implies the exercise and possible violation of reproductive rights, the right to identity (which includes the right to a name, filiation, knowledge of biological origin and nationality), the right to privacy, the right to family unity, among others. On the other hand, in some cases of surrogacy, the pregnant women become attached to the child, who is taken from their arms because there is a prior agreement. In other cases, the children are born with pathologies and the contracting partners do not want them; then, as the agreement has no legal framework, the children are left in a state of defencelessness. In all these cases there are ethical-legal implications that need to be addressed. This article aims to reflect on the need for bioethics to adequately regulate assisted reproduction techniques and surrogate management, based on the analysis of real cases such as the twins with hydrocephalus who were abandoned or the child who was born with the help of three parents in Mexico; we will also look at the legislation of other countries, such as England, to suggest the ethical-legal dilemmas that may arise and their possible solution.